Studies on the Biodiversity of Aseptate Gregarine Parasite From the Oligochaete Host of Bangladesh (Bangladesh Journal of Zoology, 2012)
Biodiversity studies in search of endoparasitic acephaline gregarines of the earthworms of Dhaka, Bangladesh, revealed a new species under the genus Nematocystis Hesse, 1909. The species was obtained from the seminal vesicles of the earthworm Metaphire peguana Rasa, 1890. It is a perfectly ribbon like organism, solitary, cylindrical, with several bulges and foldings in the middle portion of the body, especially in mature forms. Mature gamont measures 1955.85-1989.0 (1970.215 ± 13.830) ?m in length and 48.62-53.04 (51.714 ± 2.135) ?m in width. Nucleus small and rounded, measures 26.52-33.15 (29.835 ± 2.992) ?m in length and 17.68-22.01 (19.448 ± 2.282) ?m in width. Gametocysts spherical with two approximately equal sized gametocytes. It measures 110.05- 121.55 (116.24 ± 4.908) ?m in length and 88.04-99.45 (93.925 ± 5.823) ?m in  width. Oocysts biconical, measuring 22.1-30.94 (26.962 ± 3.870) ?m × 11.05- 15.47 (13.26 ± 2.08) ?m. DOI: http://dx.doi.org/10.3329/bjz.v40i1.12894 Bangladesh J. Zool. 40(1): 51-58, 2012